2008
DOI: 10.1007/s00259-008-0961-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined evaluation of preoperative FDG uptake on PET, ground-glass opacity area on CT, and serum CEA level: identification of both low and high risk of recurrence in patients with resected T1 lung adenocarcinoma

Abstract: Combined evaluation of preoperative FDG uptake, GGO, and serum CEA level may enable patients with T1 lung adenocarcinoma at low risk and at high risk of postoperative recurrence to be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Using the optimal cut-off value identified in our study (>2.12 ng/mL), we found that serum CEA level was associated not only with IAC, but also with poor overall survival in T1 lung adenocarcinoma patients [11, 35]. Several studies have shown a correlation between high preoperative serum CEA levels and poor survival after lung cancer resection, which is consistent with our results [7, 11, 36]. …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Using the optimal cut-off value identified in our study (>2.12 ng/mL), we found that serum CEA level was associated not only with IAC, but also with poor overall survival in T1 lung adenocarcinoma patients [11, 35]. Several studies have shown a correlation between high preoperative serum CEA levels and poor survival after lung cancer resection, which is consistent with our results [7, 11, 36]. …”
Section: Discussionsupporting
confidence: 91%
“…However, the optimal cut-off value for serum CEA level varies in the literature [7, 9]. Using the optimal cut-off value identified in our study (>2.12 ng/mL), we found that serum CEA level was associated not only with IAC, but also with poor overall survival in T1 lung adenocarcinoma patients [11, 35].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, solid lung tumors such as squamous cell carcinoma, and large/small cell carcinoma are often difficult to diagnose when the tumor has a small diameter without gradualgrowth characteristics, as it may be difficult to discriminate these masses from inflammatory lung nodules [33,34]. Given that elevated serum CEA was found to be a prognostic factor for LC, the combination of CT and serum CEA assays for LC screening may prove beneficial [35,36]. It must be noted however that the serum CEA levels in early stage LC are usually within the normal range.…”
Section: Discussionmentioning
confidence: 96%
“…If cancer is found at surgery, yearly surveillance should be continued for at least 3 years to assess for the development of new cancers. As with single PSNs that are 810 mm, a PET scan should be done before surgery in order to optimize pre-operative assessment [25] .…”
Section: Recommendationmentioning
confidence: 99%